Ensuring gender equality as a goal of sustainable development (case of Latin America) - O. V. Averina (Ибероамериканские тетради, 2019)
Sustainable development of any country involves the effective use of the intellectual and economic potential of all its citizens, men and women. That is why the achievement of gender symmetry is one of the priority tasks for the world community. There is an impressive body of norms, standards and principles related to the problems of gender equality, which the UN defends in the world. The author analyzes the impact of these documents and the activities of international organizations on the development and implementation of gender policy inLatin America. The paper examines specialized national mechanisms and plans for the promotion of women’s rights and the elimination of discrimination, etc. Such an analysis provides a very broad picture of the results achieved, as well as the problems and contradictions that Latin American society faces today in integrating women into the process of socioeconomic development.